Demonstrative educational haptic manipulator robot: a teaching aid in Mechatronics - Pereira, Afonso (2022)
In this paper it is presented an educational experiment, that consists of a mechatronic system applied to demonstrate concepts such as prototyping, control, haptic feedback and the use of different sensors and actuators. The described mechatronic system is based on the use of two identical manipulators, being physical devices commonly used in the industry. The physical components of the manipulators were 3D printed, being the original model of each manipulator the "EEZYBotArm MK2". This, already existent prototype was modified, with the necessary changes, to fulfill the requisites of the proposed system, being included load cells to provide measurement of the applied forces, and the robot gripper was also modified, being applied an electromagnetic actuator.